Taxonomic revision of the Dasypus kappleri complex, with revalidations of Dasypus pastasae (Thomas, 1901) and Dasypus beniensis Lönnberg, 1942 (Cingulata, Dasypodidae) - Feijó, Anderson; Cordeiro-Estrela, Pedro (Zootaxa, 2016)
Dasypus kappleri is the largest species of the genus Dasypus and is restricted to the Amazonian rainforest biome. Over the last century, related taxa have been described and synonymized without comprehensive analyses, and the current classification involving two subspecies, Dasypus k. kappleri and Dasypus k. pastasae, has never been revised. The aim of this work is to clarify the taxonomy of Dasypus kappleri through integrative morphological and morphometric analyses. We examined 70 specimens housed in scientific collections as well as photographs of the type specimens of five nominal taxa. Three methodologies (discrete characters, linear and geometric morphometrics) were employed. All results converged on the recognition of three allopatric groups, each with diagnostic qualitative and quantitative traits, that we recognize as full species: Dasypus kappleri Krauss, 1862, occurs in the Guiana shield; Dasypus pastasae (Thomas, 1901) is distributed from the eastern Andes of Peru, Ecuador, Colombia, and Venezuela south of the Orinoco River into the western Brazilian Amazon; and Dasypus beniensis Lönnberg, 1942, occurs in the lowlands of Amazonian Brazil and Bolivia to the south of the Madre de Dios, Madeira, and lower Amazon rivers. This revision raises to nine the number of living species of Dasypus.